Analysis of Means (ANOM) based on the Size Biased Lomax Distribution - Subba Rao, R; Naga Durgamamba, A; Prasad, G; R.L. Kantam, R (International Journal of Engineering and Technology, 2018)
A life time random variable which assumes a size biased Lomax model is considered as a measurable quality characteristic. In this paper,Decision lines are estimated using Analysis of Means (ANOM) technique for size biased Lomax distribution. Results are discussed through examples based on real data. Also, the results are compared with that of Shewart control charts.Â Â